Aspects of British economic history, 1918-1925 - Pigou, A. C. (London : F. Cass, 1971)
The period covered by this study extends from the Armistice in November 1918 to the restoration of the gold standard in great Britain in April 1925. The object of the study is to set out and, so far as may be, to explain the facts of the immediate post-war period, not primarily for their own sake, but in the hope that knowledge about them may provide some guidance for current post-war policy.
Reprint of the 1947 ed.
Includes bibliographical references and index.
aia 09/05/2018
Loans
Keywords: Economic history; Great Britain